Pengaruh Kompetensi, Budaya Organisasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada Glory Ocean Lines Medan - Hutapea, Jonathan Herman; Hendry, Hendry; Johan, Johan; Antar Eli Gulo; Michael Chandra; Efandri Agustian (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze the influence of competency, organizational culture, and work environment on employee job satisfaction at PT. Glory Ocean Lines Medan, both partially and simultaneously. The research method used is quantitative research with an explanatory research approach. The study population was 61 employees, and the entire population was used as the research sample. Data collection was conducted through questionnaires, interviews, and documentation. While data analysis used multiple linear regression analysis assisted by the SPSS program version 26, which includes the coefficient of determination test, F test, and t test. The results showed that competency has a positive and significant effect on employee job satisfaction with a calculated t value of 3.247 and a significance of 0.002, organizational culture has a positive and significant effect on employee job satisfaction with a calculated t value of 2.269 and a significance of 0.027, and the work environment has a positive and significant effect on employee job satisfaction with a calculated t value of 2.681 and a significance of 0.010. Simultaneously, competency, organizational culture, and the work environment have a positive and significant effect on employee job satisfaction, with a calculated F-value of 20.165 and a significance level of 0.000. The Adjusted R-Square value of 0.489 indicates that competency, organizational culture, and the work environment explain 48.9% of the variation in employee job satisfaction, while well-being is influenced by other factors outside the study, accounting for 51.1%. The conclusion of this study indicates that improving competency, organizational culture, and a conducive work environment can improve employee job satisfaction at PT. Glory Ocean Lines Medan.  Keywords: Organizational Culture, Job Satisfaction, Work Environment, Human Resources